The effectiveness of marketing and promotion activities in the Perpustakaan Sultan Badlishah, UiTM Kedah / Farleen Azrina Zamberi - Zamberi, Farleen Azrina (2011)
Marketing and promotion activities are very important to the library in order to promote the products and also services. The marketing and promotion activities not only dine manually but also electronically. This study is aim to seek for the effectiveness of marketing and promotion methods in Perpustakaan Sultan Badlishah (PSB). The independent variables that had been determined for this study are librarians' skill, promotion methods, users' needs and information technology (In. Moreover, in order to gain data, the questionnaires are distributed to the students from Diploma in Information Management (DIM) part 3 and Bachelor in Information Studies (BIS) part 4. They are choosing because, during this semester, they are learning about marketing in the libraries. So, they are able to give accurate and precise answers. For analyzing data, the Statistical Package for the Social Science (SPSS) version 14.0 will be used.